Horta escolar : possibilidades de um recurso pedagógico interdisciplinar em uma escola integral - Rodrigues, Katiuscia (2018)
This work presents, as a research proposal, the implantation of a school vegetable garden in the integral school located at the municipality of Várzea Grande, Mato Grosso. It aimed to stimulate the active participation in the students’ learning in the elective discipline Wave Fitnnes, using the interdisciplinarity, and the collaborative work with the, Chemistry, Mathematics and Physical Education subjects. The research, conducted at 2017, was developed with 23 students and 3 teachers using elements of participatory research and qualitative analysis of the data produced. The work intervention resulted in students and teachers active involvement, using a vegetable garden as a teaching-learning tool. Considering the results of this research, a digital guide was developed using the ISSU program, with the purpose of using the vegetable garden as a pedagogical resource, guiding the planning and implementation of the same in the school spaces, involving interdisciplinary and collaborative work.